Pemberdayaan Masyarakat Berbasis Perlindungan Anak dan Ekonomi Lokal: Implementasi Program Desa Ramah Anak dan Video Profil UMKM di Dukuh Sewan, Desa Mayungan - Uci Rahmah Dini; Za’idah Nuhaa Athifah; Fahmi Ilham Mufid; Luthfiyah Nurhanifah; Laela Nur Azizah; Rini Lovita; Zulfa Nur Hasanah; Assyifa Dhian Dhani; Zaky Fawwaaz Maulana Al Ghozi; Akhdan Raditya Abiyyu; Nirmala Himmatul Husna (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Village development that focuses solely on economic aspects without adequate attention to child protection tends to produce imbalanced and less sustainable community empowerment. This community service program aimed to implement a Child-Friendly Village program while developing promotional video profiles for micro, small, and medium enterprises (MSMEs) in Dukuh Sewan, Mayungan Village, Ngawen Subdistrict, Klaten Regency, Central Java. A descriptive qualitative approach combined with participatory community empowerment principles was applied, involving village officials, PKK and Posyandu administrators, MSME owners, and local residents as active participants rather than mere program recipients. Data were gathered through direct observation, in-depth interviews, focus group discussions, and documentation, then analyzed descriptively and validated through source and method triangulation. The Child-Friendly Village program was realized through two routine activities, Fun Game and Pojok Baca (Reading Corner), designed to strengthen children's motor skills, cooperation, and reading interest. Meanwhile, the MSME video profile program produced short promotional videos for two local businesses, Dapur Gamelan and Sate Kere Bobo Bu Narti, to enhance brand awareness and expand their digital market reach through social media. The results show that integrating child protection efforts with digital-based economic empowerment can mutually reinforce and strengthen the social and economic